Slope Entropy Characterisation: An Asymmetric Approach to Threshold Parameters Role Analysis - Mahdy Kouka; David Cuesta-Frau; Vicent Moltó-Gallego (Entropy, 2024)
Slope Entropy (SlpEn) is a novel method recently proposed in the field of time series entropy estimation. In addition to the well-known embedded dimension parameter, m, used in other methods, it applies two additional thresholds, denoted as <semantics>δ</semantics> and <semantics>γ</semantics>, to derive a symbolic representation of a data subsequence. The original paper introducing SlpEn provided some guidelines for recommended specific values of these two parameters, which have been successfully followed in subsequent studies. However, a deeper understanding of the role of these thresholds is necessary to explore the potential for further SlpEn optimisations. Some works have already addressed the role of <semantics>δ</semantics>, but in this paper, we extend this investigation to include the role of <semantics>γ</semantics> and explore the impact of using an asymmetric scheme to select threshold values. We conduct a comparative analysis between the standard SlpEn method as initially proposed and an optimised version obtained through a grid search to maximise signal classification performance based on SlpEn. The results confirm that the optimised version achieves higher time series classification accuracy, albeit at the cost of significantly increased computational complexity.